Entrepreneurial leadership learning: in search of missing links - Bagheri, Afsaneh; Lope Pihie, Zaidatol Akmaliah (Elsevier, 2010)
The main purpose of this study was to identify the processes of entrepreneurial learning that contribute to university students’ entrepreneurial leadership learning and development. Fourteen undergraduates were purposefully selected as the participants. Analysis of the data obtained through semi-structured interviews indicated entrepreneurial leadership learning diversity among the students. Furthermore, social interaction, observation, and reflection emerged as the processes that significantly contribute to students’ entrepreneurial leadership learning.